Composite cross-linked hole transport layer based on benzophenanthrene derivative and preparation method of composite cross-linked hole transport layer
Through the composite cross-linking process of multifunctionalized benzophenone derivatives with cross-linking small molecules and photoinitiators, the problems of low mobility and poor thermal stability of the hole transport layer in perovskite solar cells were solved, and a hole transport layer with high mobility and low temperature process was achieved, providing performance and cost solutions for the commercialization of perovskite solar cells.
Patent Information
- Application Number
- CN202510678494.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-09-12
AI Technical Summary
The hole transport layer materials in existing perovskite solar cells have problems such as low mobility, poor thermal stability and complex preparation process, which limit the performance and commercialization process of the device.
A composite cross-linking process of multifunctionalized triphenylene derivatives, cross-linking small molecules and photoinitiators is adopted. Through molecular design and low-temperature cross-linking technology, a one-dimensional carrier transport channel is constructed to form a hole transport layer with high mobility and high stability.
The hole mobility was increased to 3.48×10-2cm2V-1s-1, and the cross-linking temperature was reduced to 80-100°C, making it suitable for heat-sensitive substrates, optimizing the performance and stability of the device and reducing the preparation cost.
Smart Images

Figure CN120623028A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hole transport materials, and specifically relates to a composite cross-linked hole transport layer based on triphenylene derivatives and a preparation method thereof. Background Art
[0002] Perovskite solar cells (PSCs) are considered to be a core candidate for the next generation of photovoltaic technology due to their high photoelectric conversion efficiency (>26%), low preparation cost and solution processability. However, their commercialization process is limited by the long-term stability of the device, among which the performance defects of the hole transport layer (HTL) are particularly prominent. Traditional HTL materials such as Spiro-OMeTAD rely on hygroscopic dopants (such as Li-TFSI and tBP), which easily trigger perovskite layer hydrolysis and ion migration, resulting in device efficiency degradation; at the same time, their intrinsic hole mobility is low (~10-4cm2 V-1s-1), which limits the charge extraction efficiency.
[0003] To improve HTL stability, cross-linked materials form a three-dimensional network structure through photo- and thermal-induced polymerization, significantly enhancing the film's solvent resistance and wet-heat stability. However, these materials face two major bottlenecks: low mobility: the increased molecular rigidity after cross-linking hinders carrier transport, resulting in hole mobilities generally below 10-5cm2 V-1s-1; and high-temperature process limitations: conventional cross-linking requires heat treatment above 120°C, which is incompatible with flexible substrates and the thermally sensitive nature of perovskites (decomposition temperature <150°C), and can easily lead to interface defects.
[0004] Recent studies have attempted to construct ordered transport channels by introducing self-assembling molecules (such as discotic liquid crystals), but have faced the following problems: single molecular design: the side chain functions of existing self-assembling molecules (such as HAT6) are limited, making it difficult to optimize both mobility and cross-linking ability; process complexity: reliance on external cross-linkers (such as bismaleimide) and multiple energy inputs (light / heat synergy), which increases preparation costs; interface energy level mismatch: insufficient energy level synergy between the self-assembling molecules and the cross-linking network, resulting in interface composite loss.
[0005] Therefore, there is an urgent need to develop an HTL material that combines high mobility, low-temperature cross-linking and endogenous stabilization, and to overcome the performance defects of the hole transport layer (HTL) through molecular structure innovation and process simplification. Summary of the Invention
[0006] The purpose of the present invention is to solve the problem that existing perovskite solar cell devices lack an HTL material with high mobility, low-temperature cross-linking and endogenous stabilization.
[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0008] The first aspect of the present invention provides a triphenylene derivative, the general structural formula of which is:
[0009] (I) 2,6,11-tris(fluoroalkoxy)-3,7,10-trialkoxytriphenylene, the structure of which is shown in Formula I:
[0010] Wherein, R1 is a C3-C6 fluoroalkoxy group containing 1-3 fluorine atoms, and R2 is a C4-C8 straight-chain alkoxy group;
[0011] (II) 2,6,11-trialkoxy-3,7,10-tri(alkenylalkoxy)triphenylene, the structure of which is shown in Formula II:
[0012] Among them, R3 is a C4-C8 straight-chain alkoxy group, and R4 is a C3-C6 alkenyl alkoxy group containing a terminal double bond.
[0013]
[0014] Preferably, among the triphenylene derivatives,
[0015] In formula III, R3 is 5-fluoropentyloxy (-O-(CH2)3CF2H), R4 is hexyloxy (-O-C6H 13 );
[0016] In formula II, R5 is hexyloxy (-O-C6H 13 ), R6 is pent-4-en-1-oxy (-O-(CH2)2CH=CH2)
[0017] The second aspect of the present invention provides a composite cross-linked hole transport layer based on the above-mentioned triphenylene derivative, characterized in that it comprises the following components: a triphenylene derivative, a cross-linking small molecule and a photoinitiator.
[0018] Preferably, the photoinitiator is OPPI (4-octyloxydiphenyliodonium hexafluoroantimonate), and the cross-linking small molecule is Vp-TPD (N,N′-di-p-tolyl-N,N′-bis(4-vinylphenyl)-4,4′-benzidine).
[0019] Preferably, the mass of the triphenylene derivative is 5 to 30% of the mass of the cross-linked small molecule; the mass of the photoinitiator is 8 to 10% of the mass of the cross-linked small molecule.
[0020] The third aspect of the present invention provides a method for preparing the composite cross-linked hole transport layer, which comprises the following steps:
[0021] (1) dissolving a cross-linked polymer, a triphenylene derivative, and a photoinitiator in an organic solvent to prepare a mixed solution with a concentration of 1.0 to 3.0 mg / mL;
[0022] (2) spin coating the mixed solution on the substrate surface to form a liquid film;
[0023] (3) UV treatment of liquid film
[0024] (4) The light-treated film is heat-treated to complete cross-linking and molecular self-assembly.
[0025] Specifically, the organic solvent in step (1) is at least one of toluene, chlorobenzene, chloroform, dichloromethane, tetrahydrofuran, N-methylpyrrolidone or o-dichlorobenzene.
[0026] Specifically, the light source of the light treatment in step (3) is 365nm, 4W, and the illumination time of the light treatment is 20 to 40s;
[0027] Specifically, the heat treatment temperature is 80-100° C., and the heat treatment holding time is 20-40 minutes.
[0028] The fourth aspect of the present invention provides the application of the hole transport layer described in the above technical solution in a perovskite solar cell. There is no special limitation on the application operation of the hole transport layer in the perovskite solar cell, and the application operation familiar to those skilled in the art can be adopted.
[0029] Beneficial effects
[0030] This invention achieves significant breakthroughs in hole transport layer (HTL) performance, device stability, and process economics through the molecular design and composite crosslinking process optimization of multifunctionalized triphenylene derivatives. The fluorine-containing side chains of F-HAT enhance intermolecular forces and regulate the temperature range of the molecular liquid crystal phase; while V-HAT, with side chains containing alkenyl double bonds, can undergo spontaneous crosslinking reactions. By constructing a one-dimensional carrier transport channel within the crosslinked network, the hole mobility is increased to 3.48×10 -2 cm 2 V -1 s -1 The cross-linking temperature is reduced to 80-100°C, avoiding thermal decomposition of the perovskite layer (such as MAPbI3), making it suitable for heat-sensitive substrates (such as PET and PI). The synergistic optimization of the hole transport layer's "high mobility-high stability-low temperature process" is achieved, providing a solution that combines performance, cost and environmental benefits for the commercialization of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a synthetic route diagram of Example 1-2;
[0032] Figure 2 AFM images and water contact angle measurements of the cross-linked hole transport layer before and after doping with triphenylene derivatives;
[0033] Figure 3 UV and UPS diagrams of HTL doped with F-HAT and V-HAT;
[0034] Figure 4 JV curves of single-carrier devices prepared with the addition of F-HAT and V-HAT;
[0035] Figure 5 JV curve of the perovskite solar cell device prepared for application example. DETAILED DESCRIPTION
[0036] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention.
[0037] Example 1
[0038] A triphenylene derivative (F-HAT) comprises the following steps:
[0039] 1) Catechol (11.01 g, 0.1 mol), 75 mL of acetone, and cetyltrimethylammonium bromide (1% of the amount of the catechol substance) were sequentially added to a reaction apparatus equipped with a stirrer, a spherical condenser, and a 250 mL three-necked flask; the temperature was raised to 60° C. and refluxed, and then an aqueous solution of sodium carbonate (15.9 g, 0.15 mol) and KI (1% of the amount of the catechol substance) was added. Then, n-hexyl bromide (33.01 g, 0.2 mol) was added, and the temperature was raised to 80° C. and refluxed for 24 h. After the reaction was complete, the reactants were poured into a Buchner funnel and filtered with suction. The solvent was removed by rotary evaporation under reduced pressure, and then separated by column chromatography to obtain o-hexyloxyphenol (11.658 g, 0.06 mol), a colorless, transparent liquid;
[0040] 2) The colorless, transparent liquid o-hexyloxyphenol (6.99 g, 0.036 mol) and anhydrous dichloromethane (DCM) (35 mL) obtained in step 1) were added to a four-necked flask, and the reaction apparatus was ventilated three times to maintain a nitrogen environment. Concentrated sulfuric acid (98%, 0.5 mL) was added with magnetic stirring and stirring in an ice-water bath, and then anhydrous ferric chloride (17.51 g, 0.108 mol) was slowly added. The reaction was carried out at room temperature for 2 to 3 hours, and the nitrogen environment was maintained throughout the process. After the raw materials reacted completely, the substrate in the three-necked flask was poured into 350 mL of icy methanol, filtered, and the solvent was evaporated under reduced pressure. The mixture was separated by column chromatography to obtain an off-white solid 3,7,10-tris(hexyloxy)-2,6,11-trihydroxytriphenylene (2.46 g, 0.012 mol);
[0041] 3) Under nitrogen, 0.8 g (1.39 mmol) of 3,7,10-tris(hexyloxy)-2,6,11-trihydroxytriphenylene and 0.005 g (0.0139 mmol) of cetyltrimethylammonium bromide (CTAB) were added sequentially to a 50 mL three-necked flask containing a stirrer and a spherical condenser. 40 mL of anhydrous N,N-dimethylformamide (DMF) was added to completely dissolve the mixture. 1.73 g (12.48 mmol) of potassium carbonate was then added and heated to reflux. After 3 h, 1.06 g (6.24 mmol) of 1-bromo-5-fluoropentane was added to the reaction vessel and allowed to react for 24 h. The reaction progress was monitored by TLC. After completion, the reaction solution was poured into 200 mL of saturated brine and extracted multiple times with 100 mL of ethyl acetate. The organic phases were combined, extracted multiple times with deionized water, and finally dried over anhydrous sodium sulfate. The sodium sulfate was removed by filtration, and the product was separated and extracted by column chromatography (eluent: dichloromethane: petroleum ether = 2:1) to obtain 0.528 g of 2,6,11-tris((5-fluoropentyl)oxy)-3,7,10-tris(hexyloxy)triphenylene.
[0042] Example 2
[0043] A triphenylene derivative (V-HAT)
[0044] The preparation method of o-hexyloxyphenol and 3,7,10-tri(hexyloxy)-2,6,11-trihydroxytriphenylene is consistent with that in Example 1, and the specific preparation steps are as follows:
[0045] Under nitrogen, 0.576 g (1 mmol) of 3,7,10-tris(hexyloxy)-2,6,11-trihydroxytriphenylene and 0.004 g (0.01 mmol) of cetyltrimethylammonium bromide (CTAB) were added sequentially to a 50 mL three-necked flask equipped with a stirrer and a spherical condenser. 40 mL of anhydrous N,N-dimethylformamide (DMF) was added to completely dissolve the mixture. 0.829 g (6 mmol) of potassium carbonate was then added and heated to reflux. After 3 hours, 0.596 g (4 mmol) of 5-bromopentene was added and allowed to react for 24 hours. The reaction progress was monitored by TLC. After completion, the reaction solution was extracted with 100 mL of ethyl acetate several times. The organic phases were combined and extracted several times with deionized water. Finally, the mixture was dried over anhydrous sodium sulfate and the product was isolated by column chromatography (eluent: dichloromethane:petroleum ether = 1:2). The separated product was recrystallized from ethanol and isopropanol to obtain 0.55 g (0.7 mmol) of 2,6,11-tri(hexyloxy)-3,7,10-tri(pent-4-ene-1-oxy)triphenylene.
[0046] Example 3
[0047] A composite cross-linked hole transport layer based on a triphenylene derivative (F-HAT) comprises the following steps:
[0048] (1) dissolving a triphenylene derivative F-HAT, a photoinitiator OPPI, and a cross-linking small molecule Vp-TPD in chlorobenzene to prepare a mixed solution; the triphenylene derivative F-HAT accounts for 10% of the cross-linking small molecule weight, and the photoinitiator accounts for 10% of the cross-linking small molecule weight;
[0049] (2) The mixed solution obtained in step (1) is spin-coated on a substrate or a film, and then irradiated with ultraviolet light for 30 seconds (365 nm, 4 W) in a glove box and heat-treated at 100° C. for 30 minutes to obtain a hole transport layer.
[0050] Example 4
[0051] A composite cross-linked hole transport layer based on a triphenylene derivative (V-HAT) comprises the following steps:
[0052] (1) dissolving a triphenylene derivative V-HAT, a photoinitiator OPPI, and a cross-linking small molecule Vp-TPD in chlorobenzene to prepare a mixed solution; the triphenylene derivative F-HAT accounts for 10% of the cross-linking small molecule weight, and the photoinitiator accounts for 10% of the cross-linking small molecule weight;
[0053] (2) The mixed solution obtained in step (1) is spin-coated on a substrate or a film, and then irradiated with ultraviolet light for 30 seconds (365 nm, 4 W) in a glove box and heat-treated at 100° C. for 30 minutes to obtain a hole transport layer.
[0054] Comparative Example
[0055] A method for preparing a hole transport layer comprises the following steps:
[0056] (1) mixing a cross-linking small molecule Vp-TPD, a photoinitiator OPPI, and an organic solvent chlorobenzene to obtain a mixed solution; wherein the amounts of the cross-linking small molecule Vp-TPD, the photoinitiator OPPI, and the organic solvent are the same as those in Example 1 (i.e., only the central plane molecule is omitted compared to Example 1);
[0057] (2) The mixed solution obtained in step (1) was spin-coated on a glass substrate, and then irradiated with ultraviolet light for 30 seconds (365 nm, 4 W) in a glove box and heat-treated at 100° C. for 30 minutes to obtain a hole transport layer.
[0058] In order to explore the effect of adding triphenylene derivatives on the film morphology and hydrophobicity, atomic force microscopy (AFM) and contact angle test analysis were used. Figure 2The test results show that the root mean square roughness of the VP-TPD film is 3.16nm. After adding the three molecules, the root mean square roughness of the film is reduced to 2.87nm and 2.68nm, respectively. This shows that the addition of triphenylene derivatives has no effect on its film-forming properties. Blending and cross-linking also help reduce film roughness. At the same time, a uniform and smooth HTL is also more conducive to reducing interfacial recombination.
[0059] In PSCs, HTL hydrophobicity is critical to device stability. Water contact angle test is usually used to determine the strength of hydrophobicity. Figure 2 As shown in the figure, the water contact angle of the film prepared by VP-TPD is 83.41°, and the water contact angles of the films doped with F-HAT and V-HAT are 79.78° and 81.50°, respectively. The addition of F-HAT and V-HAT reduces its hydrophobicity, but overall, after the addition of the two molecules, the film still has good hydrophobicity.
[0060] The performance of the hole transport layer prepared in Examples 1-2 and the comparative example was tested, and the hole carrier mobility was tested using the space charge limited current method (SCLC). The voltage-current curves are shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that the introduction of triphenylene derivatives F-HAT and V-HAT can increase the carrier mobility of Vp-TPD from 6.96×10 -3 Increased to 3.48×10 -2 cm 2 V -1 s -1 .
[0061] The energy level distribution of the doped film was calculated by the film UV-visible absorption spectrum and UPS test, such as Figure 3 As shown in Figure 2, triphenylene derivatives act as a p-type dopant, which reduces the interface energy barrier and makes it easier for holes to transfer from the perovskite layer to the HTL layer.
[0062] Application Example 1
[0063] The hole transport layer prepared in Example 1 is applied to a perovskite solar cell device, and the specific steps are as follows:
[0064] (1) mixing a triphenylene derivative F-HAT, a crosslinking small molecule Vp-TPD, a photoinitiator OPPI and an organic solvent chlorobenzene to obtain a mixed solution; wherein the triphenylene derivative accounts for 5% of the crosslinking small molecule by weight; and the photoinitiator OPPI accounts for 10% of the crosslinking small molecule by weight;
[0065] (2) Spin-coating the mixed solution obtained in step (1) on an ITO glass substrate, irradiating the substrate with ultraviolet light for 30 seconds (365 nm, 4 W) in a glove box, and heat-treating the substrate at 100° C. for 30 minutes to obtain a hole transport layer;
[0066] (3) dispersing nano-alumina with isopropyl alcohol, and spin-coating the nano-alumina film on the hole transport layer obtained in step (2) in a glove box;
[0067] (4) In a glove box, a perovskite film is spin-coated on the aluminum oxide film obtained in step (3) in a one-step method, and then irradiated with ultraviolet light for 30 seconds in the glove box and annealed at 100° C. for 30 minutes to obtain a perovskite film; wherein the structure of the perovskite film is Cs 0.05 (FA 5 / 6 MA 1 / 6 ) 0.95 Pb(I 0.85 Br 0.15 )3;
[0068] (5) using chlorobenzene to disperse the interface modification material 1,3-propane-diammonium iodide, spin-coating the modification layer on the perovskite film obtained in step (4) in a glove box, and then annealing at 100° C. for 5 minutes to obtain an interface modification layer on the perovskite;
[0069] (6) When the vacuum degree is 6×10 -4 The electron transport layer C was evaporated under the conditions of Pa 60 (with a thickness of 20 nm) and an electron blocking layer BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, with a thickness of 6 nm) are formed on the modified layer obtained in step (5) to obtain a perovskite solar cell device.
[0070] Figure 5 Contains the JV curve of the perovskite solar cell device prepared in Application Example 1. Figure 4 It can be seen that the efficiency of the optimized device prepared by F-HAT doping is 18.46%, J SC 21.50mAcm -2 、V OC The V-HAT doping optimized device has a V-HAT doping efficiency of 18.64% and a J SC 21.53 mA cm -2 、V OC The device achieved a peak voltage of 1.096V and a fill factor of 79.10%, demonstrating improvements across all performance parameters. The increase in short-circuit current is primarily due to improved film quality, resulting in greater visible light absorption. The increase in open-circuit voltage is attributed to p-type doping, which optimizes the energy level between the HTL and perovskite layers and improves carrier mobility.
[0071] It can be seen from the above embodiments and application examples that the hole transport layer prepared by the preparation method provided by the present invention has a high hole mobility.
[0072] The above is only the best embodiment of the present invention. It should be noted that, for those skilled in the art, without departing from the principles of the present invention, several modifications or equivalent substitutions can be made to the technical solution of the present invention, which can still achieve the technical effects of the present invention and should also be considered to fall within the scope of protection of the present invention.
Claims
1. A triphenylene derivative, characterized in that Its general structural formula is selected from any one of the following: (I) 2,6,11-tris(fluoroalkoxy)-3,7,10-trialkoxytriphenylene, the structure of which is shown in Formula I: Wherein, R3 is a C3-C6 fluoroalkoxy group containing 1-3 fluorine atoms, and R4 is a C4-C8 straight-chain alkoxy group; (II) 2,6,11-trialkoxy-3,7,10-tri(alkenylalkoxy)triphenylene, the structure of which is shown in Formula II: Among them, R5 is a C4-C8 straight-chain alkoxy group, and R6 is a C3-C6 alkenyl alkoxy group containing a terminal double bond.
2. The triphenylene derivative according to claim 1, characterized in that: In formula I, R1 is 5-fluoropentyloxy (-O-(CH2)3CF2H), R2 is hexyloxy (-O-C6H 13 ); In formula II, R3 is hexyloxy (-O-C6H 13 ), R3 is pent-4-en-1-oxyl (-O-(CH2)2CH=CH2).
3. The composite cross-linked hole transport layer of a triphenylene derivative according to any one of claims 1 to 2, characterized in that: The invention comprises the following components: a triphenylene derivative, a cross-linking small molecule and a photoinitiator; the doping ratio of the triphenylene derivative is 5% to 30% by mass; the cross-linking small molecule is N,N'-di-p-tolyl-N,N'-bis(4-vinylphenyl)-4,4'-benzidine (VP-TPD); and the photoinitiator is 4-octyloxydiphenyliodonium hexafluoroantimonate (OPPI), and the addition amount thereof is 8% to 10% by mass of the cross-linked polymer.
4. The composite cross-linked hole transport layer according to claim 3, characterized in that: The mass ratio of the triphenylene derivative to the cross-linked polymer is 1:4 to 1:10, and the hole mobility of the hole transport layer is 2.58×10 -2 ~5.12×10 - 2 cm 2 V -1 s -1 .
5. A method for preparing a composite cross-linked hole transport layer as claimed in any one of claims 3 to 4, characterized in that: The following steps are involved: (1) dissolving a cross-linked polymer, a triphenylene derivative, and a photoinitiator in an organic solvent to prepare a mixed solution with a concentration of 1.0 to 3.0 mg / mL; (2) spin coating the mixed solution on the substrate surface to form a liquid film; (3) The liquid film is treated with ultraviolet light, and the illumination conditions are wavelength 365nm, power 4W, and time 20-40s; (4) Annealing the light-treated film at 80-100° C. for 20-40 minutes to complete cross-linking and molecular self-assembly.
6. The preparation method according to claim 5, characterized in that: The organic solvent is at least one of chlorobenzene, toluene or tetrahydrofuran, the spin coating speed is 5000-8000 rpm, and the film thickness is 60-100 nm.
7. A perovskite solar cell, characterized in that: include: A transparent conductive substrate (ITO), a composite cross-linked hole transport layer according to any one of claims 3 to 4, an aluminum oxide modified layer (Al2O3), a perovskite light absorbing layer (PVSK), an electron transport layer (C 60 / BCP) and a metal electrode (Ag); the HOMO energy level of the composite cross-linked hole transport layer is -5.23 to -5.28 eV, and the valence band energy level difference with the perovskite layer is ≤0.3 eV.
